A comparative clinical trial for evaluating the posterior palatal seal developed from the conventional method and a novel functional swallow method - Sweekriti Mishra; Ravishankar Krishna; Rashmi Badakka Mandokar; Shobhit Agarwal; Anoop Sharma; Misty Shaw (Wolters Kluwer Medknow Publications, 2022)
Aims: The aim of this in vivo study was to compare the influence of posterior palatal seal (PPS) developed from the conventional method and a novel functional swallow method on the retention of custom tray and heat cure denture base. Settings and Design: This was a nonrandomized crossover clinical trial. Materials and Methods: Twenty patients requiring maxillary complete dentures were selected. In Group 1, for all twenty patients, the PPS was developed with the conventional functional method during border molding and a conventional cast scoring was performed before processing the denture base. In Group 2, for all the twenty patients, the PPS was developed with a novel functional swallow method and the master cast was "not" scored before processing the denture base. The retention was objectively measured using a dynamometer after border molding and also after processing the denture base for both groups. Statistical Analysis Used: Independent Student's t-test and paired t-test were used for analysis. Results: The mean retention value of Group 2 was significantly higher (P < 0.001) than Group 1 at border molding and after denture base processing. Within Group 1, the retention value significantly increased (P < 0.001) from border molding to the denture base stage, whereas within Group 2, there was no significant change (P > 0.001) between the stages. Conclusions: Within the limitations of the study, the novel functional swallow method of establishing the PPS demonstrated higher retention than the conventional method both during border molding and after processing the denture base.